2002
DOI: 10.1590/s0034-70942002000600004
|View full text |Cite
|
Sign up to set email alerts
|

Comparação da qualidade do bloqueio oftálmico periconal com ropivacaína a 1% e 0,75% com punção os pontos infraorbitário lateral e medial da órbita

Abstract: RESUMO M10(R1 = 1,6; R0,75 = 3,8) e M15(R1 = 1,04; R0,75 = 2,8 U N I T E R M O S : A N E S T É S I C O S , L o c a l : r o p i v a c a í n a R1: 9.72 ± 2.38 ml and 6.96 ± 0.97 ml; and for R0.75: 12.64 ± 5.10 ml and 7.36 ± 1.07

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
1
3
0
3
Order By: Relevance
“…Because there is a great diversity of bony orbit sizes among breeds of dogs, some authors recommend administering the anesthetic solution with a volume range according to the volume tolerance and distensibility. They recommend paying special attention to avoid exaggerated iatrogenic exophthalmos and subsequent excessive increase of intraocular pressure . During the experimental infusion performed in this investigation on thirty cadavers of step 2 with different volumes of contrast medium, we have observed that the distensibility is directly related with volumetric capacity of the periorbita, as previously described .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Because there is a great diversity of bony orbit sizes among breeds of dogs, some authors recommend administering the anesthetic solution with a volume range according to the volume tolerance and distensibility. They recommend paying special attention to avoid exaggerated iatrogenic exophthalmos and subsequent excessive increase of intraocular pressure . During the experimental infusion performed in this investigation on thirty cadavers of step 2 with different volumes of contrast medium, we have observed that the distensibility is directly related with volumetric capacity of the periorbita, as previously described .…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, the volume of 0.1 mL/cm L cr was chosen because subtle exophthalmos is the ideal situation immediately after injecting local anesthetic, according to Vásquez et al . and Olmez et al …”
Section: Resultsmentioning
confidence: 99%
“…1) demonstram que o procedimento anestésico em ambos os grupos foi adequado e manteve níveis esperados para a espécie. Os valores de frequência respiratória, da PaCO 2 e do pH arterial não evidenciaram acidose respiratória, ao contrário dos resultados apresentados por Lee et al (1998) Foi possível desenvolver uma técnica de anestesia peribulbar para cães fundamentando-se na técnica de bloqueio peribulbar posterior realizada no homem, constatada como eficiente por Vásquez et al (2002). Os bloqueios foram realizados com sucesso utilizando-se agulha hipodérmica descartável 0,7mmx25mm, assim como descrito em diferentes trabalhos realizados na anestesia humana (Perello et al, 2000;Déb et al, 2001;Olmez et al, 2004).…”
Section: Resultsunclassified
“…Teve-se o cuidado de manter a agulha mais próxima à parede orbitária durante sua inserção, para evitar perfuração ocular e manter o bisel direcionado para o globo ocular, a fim de reduzir resistência durante a administração do anestésico local. O volume de anestésico local administrado em cada ponto de punção variou conforme a tolerância e a distensibilidade do espaço orbitário, como citado por Vásquez et al (2002), com o cuidado de se evitar a ocorrência de exoftalmia e o aumento excessivo da pressão intraocular. Após cada injeção, realizou-se compressão digital da órbita durante um minuto, para auxiliar na difusão da solução anestésica.…”
Section: Methodsunclassified
See 1 more Smart Citation